2017
DOI: 10.3390/app7070715
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Hexavalent Chromium Using Sorbaria sorbifolia Aqueous Leaf Extract

Abstract: Aqueous plant leaves extract (PLE) of an abundant shrub, Sorbaria sorbifolia, was explored for the reduction of hexavalent chromium, Cr(VI), to trivalent chromium, Cr(III). The effect of contact time, pH, PLE quantity, ionic strength, hardness, temperature and effective initial Cr(VI) ion concentration were tested; Cr(VI) reduction followed the pseudo-first order rate kinetics and maximum reduction was observed at pH 2. Significantly, Cr(VI) reduction efficacies varied from 97 to 66% over the pH range of 2 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…The differences in absorption intensities may be due to variation in number of functional groups corresponding to that particular wave number. Earlier studies also reported major peaks in similar regions for GT, O. gratissimum, C. citratus, C. flexuosus, and H. rosa sinensis (Dubey, Sillanpaa, & Varma, ; Irshad et al, ; Sathiyamoorthi & Sankaranarayanan, ). Interestingly, GT combinations demonstrated similar spectra, as that of GT single infusion except few additional peaks in the region 3600–4000 cm −1 that may be assigned to free OH of alcohol (Siripatrawan & Harte, ).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The differences in absorption intensities may be due to variation in number of functional groups corresponding to that particular wave number. Earlier studies also reported major peaks in similar regions for GT, O. gratissimum, C. citratus, C. flexuosus, and H. rosa sinensis (Dubey, Sillanpaa, & Varma, ; Irshad et al, ; Sathiyamoorthi & Sankaranarayanan, ). Interestingly, GT combinations demonstrated similar spectra, as that of GT single infusion except few additional peaks in the region 3600–4000 cm −1 that may be assigned to free OH of alcohol (Siripatrawan & Harte, ).…”
Section: Discussionmentioning
confidence: 67%
“…These changes may possibly affect the estimation of TPC by Folin-Ciocalteu method. (Dubey, Sillanpaa, & Varma, 2017;Irshad et al, 2018;Sathiyamoorthi & Sankaranarayanan, 2017). Interestingly, GT combinations demonstrated similar spectra, as that of GT single infusion except few additional peaks in the region 3600-4000 cm −1 that may be assigned to free OH of alcohol (Siripatrawan & Harte, 2010).…”
Section: Discussionmentioning
confidence: 70%
“…This is due to the above said reasons. The Pt/reduced graphite oxide (RGO) system showed the k app value for the reduction of individual NP is 1.11 × 10 −3 s −1 . The Ca‐AC system showed better results as compared with the literature.…”
Section: Resultsmentioning
confidence: 93%
“…The Pt/reduced graphite oxide (RGO) system showed the k app value for the reduction of individual NP is 1.11 × 10 −3 s −1 . 26 The Ca-AC system showed better results as compared with the literature. The biosourcemediated catalytic reduction of chromium (VI) yielded the k app value of 1.39 × 10 −3 s −1 .…”
Section: Catalytic Reduction Of the Tricomponent Systemmentioning
confidence: 80%
“…Furthermore, the growing interest in biological food additives has challenged the scientific community to innovate in alternative food preservation and plant crop protection systems. Thus, natural preservatives from sources like bacteria, plants and algae were reported to ensure food safety due to their antimicrobial activity against a wide spectrum of foodborne pathogens [3,4]. In this regard, dietary antioxidants (i.e., phenolic compounds) have recently attracted extensive attention because of their ubiquity in nature and their various beneficial effects, including antimicrobial, antioxidant, antiinflammatory and antiproliferative activities [5].…”
Section: Introductionmentioning
confidence: 99%